Active matrix field sequential color electrically suppressed helix ferroelectric liquid crystal for high resolution displays. Issue 5 (22nd May 2018) - Shi, Liangyu; Srivastava, Abhishek Kumar; Cheung, Alex; Hsieh, Chia‐Ting; Hung, Ching‐Lang; Lin, Ching‐Hsiang; Lin, Ching‐Huan; Sugiura, Norio; Kuo, Chia‐Wei; Chigrinov, Vladimir G.; Kwok, Hoi Sing
Abstract: In this article, we disclose a 3‐inch 250ppi active matrix field sequential color (FSC) display based on electrically suppressed ferroelectric liquid crystal (ESHFLC). ESHFLC's ultra‐fast response time ( 10 μs at 6.67 V/μm) enables the display resolution to be tripled via FSC technique. The photo‐alignment technology provides ESHFLC with optimal anchoring energy that contributes to a high contrast ratio over 10 K:1 on single pixel level measurement. A specific 3T1C pixel circuit is designed to generate continuous gray scale from FLC binary switching by utilizing the pulse width modulation concept. The low temperature poly silicon thin‐film transistor array has been used to fabricate the FSC ESHFLC display panel. We achieved an 8‐bit gray level for each color subframe, that is, R, G, and B colors that results in 24‐bit color images. We believe, because of the good optical quality and cost‐effective fabrication, this display may replace in‐plane switching or fringe‐field switching in the near future for the portable device market. Moreover, high resolution FSC ESHFLCs can find applications in the emerging virtual reality displays. Abstract : An active matrix 3‐inch field sequential color electrically suppressed helix ferroelectric liquid crystal display prototype is demonstrated via low temperature poly silicon thin‐film transistor array. 3T1C pixel circuit is designed to generate analogy gray scale by utilizing pulse width modulation method. The electrically suppressed ferroelectric liquid crystal's microsecond fast switching enables the system with 8‐bit color level for each primary color.